2005
DOI: 10.1145/1080390.1080394
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the relationships between IT infrastructure flexibility, mass customization, and business performance

Abstract: Information technology (IT) infrastructure deserves serious attention from both the practitioner and academic communities, especially concerning the factors for IT infrastructure flexibility. The issue of flexibility is viewed as a critical aspect of IT infrastructure, because organizations are faced with an ever-increasing rate of change in their business environments. One effort most business sectors have made to prepare for this change is the trend toward mass customization. Recently, many organizations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
1
33
0
5
Order By: Relevance
“…Additionally, the combination of having both technical infrastructure and human infrastructure in IT is proven by few studies that it enhances competitive advantage with their importance is found to be positive to the organisations' flexibility (Byrd and Turner, 2001;Chung et al, 2005;Fink and Neumann, 2007). Hence, Zainon and Salleh 7251 this paper can safely state that ITIF will improve effectiveness in construction organisations, as well as enhancing competitive advantage.…”
Section: Increase Effectiveness and Enhance Competitive Advantagementioning
confidence: 87%
See 4 more Smart Citations
“…Additionally, the combination of having both technical infrastructure and human infrastructure in IT is proven by few studies that it enhances competitive advantage with their importance is found to be positive to the organisations' flexibility (Byrd and Turner, 2001;Chung et al, 2005;Fink and Neumann, 2007). Hence, Zainon and Salleh 7251 this paper can safely state that ITIF will improve effectiveness in construction organisations, as well as enhancing competitive advantage.…”
Section: Increase Effectiveness and Enhance Competitive Advantagementioning
confidence: 87%
“…This fact has been examined by few researchers namely Ness (2005), Masrek andJusoff (2009), Chung et al (2003), and Chung et al (2005).…”
Section: Implication To Management Of Construction Industrymentioning
confidence: 96%
See 3 more Smart Citations